Culture of sand goby (Oxyeleotris marmoratus, Bleeker) fed with live and frozen fairy shrimp (Streptocephalus sirindhornae) - Suksomnit, A.; Pholwieng, N. (International Journal of Agricultural Technology, 2017)
This study aimed to analyze the effect of live and frozen [1]fairy shrimp (Streptocephalus sirindhornae) for the growth performance of sand goby (Oxyeleotris marmoratus) . The experiment was designed in Completely Randomized Design.The fingerlings of sand goby were fed with live artemia, live and frozen fairy shrimp of 1.5 centimeters in length which contained in a 95 cm plastic basin. Each basin carried 20 liters of water with 25 sand goby per basin. The experiment animals were fed twice daily in the morning and afternoon for 8 weeks. The average initial weights and length of fingerings were 0.63±0.00, 0.60±0.02, 0.63±0.03 g and 3.12±0.02, 3.11±0.023.11±0.02 cm., respectively. The results showed that fingering fed with live fairy shrimp gave significantly better growth than fed with artemia and frozen fairy shrimp (p<0.05). The final weights were 5.32±0.16, 2.57±0.25 and 2.54±0.22g, respectively. Meanwhile, the final lengths were 6.20±0.09, 4.90±0.14 and4.88±0.13 cm, respectively. The daily weight gains were 0.085±0.00, 0.035±0.00 and 0.026±0.02 g/day respectively; specific growth rate of 3.89±0.08, 2.51±0.12 and2.48±0.14 % per day, respectively. Survival rates were 99.00±2.00, 91.00±11.49 and 73.00±8.87 %, respectively. It is indicated that sand goby fed with live fairy shrimp yielded better growth performance.